Development of OEFPADU Syntax Biology LKPD to Improve Critical Thinking of Islamic Values and Scientific Attitud - Sanudin Sanudin; Tien Aminatun (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to produce Biology LKPD, determine the feasibility and effectiveness of the LKPD developed to increase critical thinking of Islamic value and Scientific attitude. The method used in this research is Research and Development (R & D) with the ADDIE model (Analysis, Design, Development, and Implementation, Evaluation) developed by Dick & Carry. Data analysis techniques used gain scores (Statistic analysis). Evaluation of biological LKPD products according to product feasibility experts is in the good category. According to the biology teacher, it was in the outstanding category and the students' responses were in the outstanding category. Learning using the OEFPADU LKPD syntax shows that critical thinking of Islamic values increases (the average gain score is 0.72), independent test simple t test sign. 0.000 and paired sample t-test 0.001 and observations of 7.60%. The scientific attitude of students increased by 14.30%, from the good to outstanding category with the Wiloxcon test analysis, the scientific attitude before and after using the OEFPADU syntax LKPD there was a significant difference with the Asymp results. Sig. 0.000 (<0.05). This shows that the use of OEFPADU LKPD syntax is effective in improving critical thinking skills of Islamic values ​​and scientific attitudes.